PENGARUH PELATIHAN, PENEMPATAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA HOTEL ROYAL ASNOF PEKANBARU - Citi, Mutiara; Sri, Indarti; Kurniawaty, Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study was aims to examine the effect of Training, Placement, and Work Discipline on Employees Perfomance of Royal Asnof Hotel. Pekanbaru. This research used 70 respondents as the sample. To analyze the data, this research used Multiple linear regression analysis by using Statistical Package for Social sciences (SPSS). The result of this study indicate that partially, Training have a positive and significant effect on employees performance, Placement have a significant effect on employees performance, work discipline have a significant effect on employees performance. and simultanously, all variables included have a significant effect on Employees performance.Keywords : Training, Work Discpline, Employee Performance